An Analysis of Balanced Scorecard Implementation as A Performance Evaluation Tool for Training Programs at the Department of Manpower, Pematangsiantar City, 2023 – 2024 - Sifa Aulia Shafira Guechi; Wico J Tarigan; Sri Martina (Jurnal Ilmiah Accusi, 2025)
This study aims to analyze the implementation of the Balanced Scorecard as a performance evaluation tool for job training programs at the Department of Manpower of Pematangsiantar City during 2023–2024. The Balanced Scorecard framework was applied through four perspectives: financial, customer, internal business processes, and learning and growth. The research uses a descriptive qualitative approach with primary data obtained from budget realization documents, interviews, observations, and questionnaires distributed to 139 training participants. The results show that, from the financial perspective, budget utilization in 2024 was more efficient compared to 2023. From the customer perspective, participant satisfaction regarding facilities, materials, and instructor quality was relatively high. The internal business process perspective indicates that the program was carried out systematically through structured planning, participant selection, and daily monitoring. From the learning and growth perspective, the institution demonstrated a strong commitment to competency development and collaboration with training partners. Overall, the Balanced Scorecard is proven to be effective as a performance evaluation tool and provides a comprehensive foundation for future program improvement